Surgical and pharmacological reassignment: influence on transsexual cardiovascular risk profile. Issue 11 (5th November 2017) - Ciccone, Marco M.; Loverro, Giuseppe; Scicchitano, Pietro; Loverro, Matteo; Ricci, Gabriella; Scaramuzzi, Francesca; Gesualdo, Michele; Zito, Annapaola; Campagna, Marcello; Moncelli, Michele; Nicolardi, Vittorio; Manca, Fabio; et al.
Abstract: Background/Aim: To evaluate and stratify early cardiovascular risk of transsexuals who underwent pharmacological and/or surgical gender reassignment. Methods: Fifty‐six transsexuals were divided into two groups: group 1 – underwent gonadectomy (orchiectomy for transwomen and hystero‐annessiectomy for transmen); group 2 – hormone replacement therapy alone. All participants underwent carotid artery intima‐media thickness (C‐IMT) and flow‐mediated vasodilation (FMD) of brachial artery evaluations. Results: FMD was lower in patients who had undergone gonadectomy compared with non‐surgically treated patients (Group 1: 5.711 vs Group 2: 7.339, P  < 0.0001). Mean C‐IMT was higher in group 1 than group 2 (group 1: 0.733 vs group 2: 0.582). The duration of hormone therapy correlates positively with mean C‐IMT ( B  = 0.001) and negatively with FMD (%) ( B  = − 0.007). Conclusions: Cardiovascular risk, which is expressed in terms of endothelial (FMD) and morphological (C‐IMT) dysfunction, increases in subjects undergoing gonadectomy compared with those receiving cross‐sex reassignment therapy alone.